Comparison of Color Quality in Tissue Preparations using Methyl Ester Sulfonate And Xylol as a Deparafinization Agent - Rahmah, Syafa Aulia; Adang Durachim; Wiwin Wiryanti; Asep Iin Nur Indra (Jurnal Kesehatan Siliwangi, 2024)
Deparaffinization is the process of decaying the remnants of paraffin in tissue preparations. Deparaffinization aims to make the dye that will be given to the preparation fully absorbed so that the preparation can be colored properly. This deparaffinization process uses xylol solution in its immersion. Methyl Ester Sulfonate (MES) is one of the vegetable oil-based anionic surfactants that can dissolve in water and has a long carbon chain that is soluble in oil and vaseline. The purpose of this study was to determine whether Methyl Ester Sulfonate can be used as a deparaffinizing agent for tissue preparations. The sample in this study was appendiceal tissue as many as 30 units, each unit of tissue made into 2 tissue preparations so that it became 60 tissue preparations, namely 30 tissues using xylol as a deparaffinizing agent and 30 tissues using methyl ester sulfonate. The parameters of this study were the clarity of the color of the nucleus and cytoplasm, the uniformity of cell color, and the contrast of the color of the nucleus and cytoplasm qualitatively and quantitatively. The statistical test used was Independent T-Test test if the data were normally distributed and Mann Whitney test if the data were not normally distributed. Based on the Independent T-Test test, the Sig value was obtained. 0.951 and 0.102, both of which are >0.05, meaning that there is no significant difference between the use of xylol and 10% methyl ester sulfonate as a deparaffinizing agent.